2011
DOI: 10.1371/journal.pone.0028910
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in Copy Number Calling by qPCR and PRT: A Matter of DNA

Abstract: The possible implication of copy number variation (CNV) in the genetic susceptibility to human disease needs to be assessed using robust methods that can be applied at a population scale. In this report, we analyze the performance of the two major techniques, quantitative PCR (qPCR) and paralog ratio test (PRT), and investigate the influence of input DNA amount and template integrity on the reliability of both methods. Analysis of three genes (PRELID1, SYNPO and DEFB4) in a large sample set showed that both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Also, efficient predigestion of gDNA improves ddPCR assay accuracy by facilitating template access. 32 Indeed, assay variability was reduced and greater consistency in estimated VCN values was observed with up to a minimum of approximately 1 ng of template (Fig. 5b).…”
Section: Discussionmentioning
confidence: 86%
“…Also, efficient predigestion of gDNA improves ddPCR assay accuracy by facilitating template access. 32 Indeed, assay variability was reduced and greater consistency in estimated VCN values was observed with up to a minimum of approximately 1 ng of template (Fig. 5b).…”
Section: Discussionmentioning
confidence: 86%
“…24 However, Fernandez-Jimenez et al demonstrated that both techniques can produce comparable DEFB4 results with the use of optimum DNA normalisation and high-quality genomic DNA. 28 Nevertheless, it is known that DEFB4 copy numbers vary between ethnicities; 29 this might account for the differences observed between the studied Iraqi and Korean populations. 24 Genetic heterogeneity was observed in the β-defensin gene cluster among 67 populations; this may have been due to selection.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, it has been suggested that real-time QPCR will perform comparably to PRT if the concentration of DNA samples is normalized to a uniform concentration, and the efficiency between the test and reference loci differ by less than 5% [18]. With knowledge of these potential variables on assay performance, we felt that it would be unfair to perform a method comparison on DNA samples that were subject to such limitations.…”
Section: Discussionmentioning
confidence: 99%